HUBUNGAN EFEKTIFITAS KOMUNIKASI INTERPERSONAL ANTARA DOSEN DAN MAHASISWA DENGAN PRESTASI AKADEMIK MAHASISWA PSIKOLOGI UNIVERSITAS SRIWIJAYA PALEMBANG - Marleni Marleni (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
This study aims to determine the relationship between the effectiveness of interpersonal communication between lecturers and students and student academic achievement. This research is based on the five aspects proposed by Kumar (2002). This study used 83 respondents, namely students of Psychology at Sriwijaya University, Jakarta. The measuring instrument used in this is the scale of the effectiveness of interpersonal communication and documentation of academic achievement in the form of a GPA. The results showed that there was a significant relationship between interpersonal communication and academic achievement with a correlation (r) = 0.883 with a significance of 0.001 where is the Spearman correlation rule, namely (rp>0). A good achievement result is not only due to the effectiveness of interpersonal communication but there are also other supporting factors, such as student motivation and good academic ability.